Too Soft Or Too Severe? Enforceable Undertakings and the Regulatory Dilemma Facing the Fair Work Ombudsman. (March 2013) - Hardy, Tess; Howe, John
This article reports on the use of enforceable undertakings by the Australian employment standards enforcement agency, the Office of the Fair Work Ombudsman (FWO), and its predecessor, the Workplace Ombudsman. Enforceable undertakings are used by the FWO as an alternative enforcement tool to court litigation in relation to breaches of the Fair Work Act 2009 (Cth), which regulates wages, working hours and other minimum employment conditions. Proponents of enforceable undertakings argue that they deliver value to regulatory agencies as a responsive alternative to traditional, punitive enforcement action. On the other hand, critics have raised concerns about the accountability and effectiveness of this enforcement tool. The authors provide a critical analysis of the FWO's use of enforceable undertakings, including consideration of the decision-making process, content, monitoring and enforcement of undertakings. The analysis is based on a review of all enforceable undertakings concluded in the period from 1 July 2008 to 30 June 2012, as well as qualitative interviews with approximately 60 inspectors, managers and lawyers of the FWO, and a number of specialist workplace relations lawyers. The article reveals that the FWO has made limited but promising use of enforceable undertakings in the review period. Through deployment of enforceable undertakings, the FWO has demonstrated that it has a mix of regulatory approaches available to it that are consistent with the key principles of responsive regulation. The number of enforceable undertakings accepted by the FWO, however, remains fairly limited. We set out a number of ways in which the regulator may maximise the utilisation of enforceable undertakings, and more fully realise the regulatory benefits of this particular compliance tool.